VIHARA DAN KOMPONENNYA SEBAGAI MITRA KERJA SEKOLAH TINGGI AGAMA BUDDHA NEGERI RADEN WIJAYA WONOGIRI JAWA TENGAH (Tinjauan Evaluasi Terhadap Tiga Wilayah Pengabdian Kepada Masyarakat STAB N Raden Wijaya) - Hesty Sadtyadi (State Institute of Islamic Studies (IAIN) Salatiga, 2015)
Tridharma community empowerment programs through college, especially community service have been carried out by STAB N Raden Wijaya Wonogiri. The program was used to implement science acquired by the lecturers and students. Particularly, the program is to improve the ability to put themselves as a religious adviser, through religion coach training, and to improve the qualification requirements of religious teachers which are still far from the requirement, as well as the utilization and improvement of its religious infrastructure, through Vihara in three areas of community service that has been done by STAB N Raden Wijaya Wonogiri. Based on the implementation, it is necessary to evaluate community service program which has been implemented in the three areas. Evaluations of the implementation of the community service program that have been implemented seem to be successful, and the people got the good result of the program. Generally, The results of the implementation of the program can be stated to be successful